2019
DOI: 10.1016/j.ijso.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cruciate Ligament reconstruction augmentation on avulsion PCL: A case series

Abstract: Introduction: Posterior Cruciate Ligament (PCL) avulsion may mimics PCL rupture with positive posterior drawer test. Treatment of choice to PCL avulsion is vary from open surgery to arthroscopic surgery. PCL reconstruction with augmentation is a rare procedure to be performed in treating PCL avulsion case. This case reported and suggested an augmentation procedure in PCL avulsion case. This study aims is to evaluate the knee functional score using augmented PCL reconstruction on PCL avulsion using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Synthetic polymers are widely used to fabricate NGCs for peripheral nerve regeneration because they have better mechanical properties to be easily fabricated into 3D structures compared to natural polymers. The recovery period of PNI is usually approximately 3-6 months (Rhatomy et al, 2019); thus, a second surgery could be avoided using biodegradable synthetic polymers. Poly (ε-caprolactone) (PCL), an FDA-approved material, is one of the most common synthetic polymers used for the fabrication of NGCs.…”
Section: Synthetic Polymer-based Conduitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic polymers are widely used to fabricate NGCs for peripheral nerve regeneration because they have better mechanical properties to be easily fabricated into 3D structures compared to natural polymers. The recovery period of PNI is usually approximately 3-6 months (Rhatomy et al, 2019); thus, a second surgery could be avoided using biodegradable synthetic polymers. Poly (ε-caprolactone) (PCL), an FDA-approved material, is one of the most common synthetic polymers used for the fabrication of NGCs.…”
Section: Synthetic Polymer-based Conduitsmentioning
confidence: 99%
“…PCL has excellent processability and compatibility ( Mobini et al, 2017 ). The NGCs made of PCL have excellent mechanical properties to offer topographical cues to axons for peripheral nerve regeneration; however, poor biodegradability is a major shortcoming ( Rhatomy et al, 2019 ) for the wide application of PCL. Sun et al (2006) transplanted PCL (Mw ¼ 66,000) scaffolds into rats and found that scaffolds remained structurally intact for 24 months.…”
Section: Synthetic Polymer-based Conduitsmentioning
confidence: 99%